2014
DOI: 10.2514/1.c032402
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Design with Active Load Alleviation and Natural Laminar Flow

Abstract: Maneuver load alleviation, gust load alleviation, and natural laminar flow are integrated into aircraft conceptual design. The concurrent design of the aircraft and its active load alleviation systems can yield significant gains. The simultaneous application of maneuver load alleviation and gust load alleviation to a short-haul aircraft leads to an 11% reduction in fuel burn and 7% reduction in direct operating cost. These savings are diminished if maneuver load alleviation and gust load alleviation are applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Through maneuver and gust load alleviation technologies, the structure mass can be significantly decreased. For example, the NASA Sugar Volt design assumes that a properly designed active load alleviation system can reduce the wing weight by 25% [24].…”
Section: Active Load Alleviationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through maneuver and gust load alleviation technologies, the structure mass can be significantly decreased. For example, the NASA Sugar Volt design assumes that a properly designed active load alleviation system can reduce the wing weight by 25% [24].…”
Section: Active Load Alleviationmentioning
confidence: 99%
“…Preliminary studies [24][25][26][27][28] have shown that the application of flap systems for static gust and low dynamics maneuver load control has a potential to reduce takeoff mass and fuel consumption of long range transport aircraft. More aggressive load alleviation techniques and a wing planform designed to exploit these functions, as well as adapted thickness respectively, stiffness distributions are expected to increase the benefits to about a 25% reduction of the mass of the wing box, which can result in a 7% reduction of the fuel consumption [29].…”
Section: Active Load Alleviationmentioning
confidence: 99%
“…The majority of research in this field employs inviscid-viscous coupling strategies, making use of boundary-layer codes for the viscous formulation and either a panel method or the Euler equations for the inviscid formulation. 30,31,32,33,34,35,36,37 Although the inviscid/viscous coupling strategies can be computationally cheaper than the higher-fidelity RANS solvers, the industry's trend toward the use of RANS solvers strongly suggests that NLF design tools should follow suit. Recent research making use of RANS solvers to optimize with transition prediction has shown promising results.…”
Section: Iib Rans-based Aerodynamic Shape Optimization For Nlfmentioning
confidence: 98%
“…Xu [2] also explores active-load-alleviation and its relationship to natural laminar flow. In this work, he found that active-load-alleviation could be used to reduce some of the structural penalties and thus create thinner wings with a higher aspect ratio.…”
Section: Introductionmentioning
confidence: 99%